PERAN GURU DALAM MENINGKATKAN KEMAMPUAN BERPIKIR LOGIS BERPIKIR KRITIS SISWA MA NW PENGADANG - Hazim Muhtarom; Baiq Yani Rosanti; Harkatun Hasanah; Wahyu Tiara Purwaningsih; Anggun Putri; Hayatunnisah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research focuses on the important role of teachers in the learning process to improve critical thinking and logical thinking skills. The focus of this research problem. The focus of this research problem is the method used by teachers to improve students' logical thinking and critical thinking abilities. The purpose of this research is to determine the learning methods used by teachers to improve students' critical thinking and logical thinking skills. The method used in this research uses a qualitative method with a descriptive type. The results of the research conducted show the importance of teachers in using learning methods to improve students' logical and critical thinking abilities